English for University Sharia Students: Theory and Practices - Badrasawi, Kamal J I; Solihu, Abdulateef; Aman, Azlina (2018)
English is the global language of today. It is expansively used as a means of communication for academic and non-academic purposes. Sharia students, with their broad knowledge of religion, can use the English language for the sake of Islam like in Da’wah, via all available media or face-to-face encounters. They would be able to do so effectively provided they are highly proficient in English. Therefore, a project is being conducted to construct a course framework in English for University Sharia students. This paper is allocated to present the theoretical foundations for these courses based on the Islamic perspective, status of the English language, and English for Specific Purposes (ESP) approach. The analytical content analysis was utilized to achieve the study objectives. The analysis showed that Islam urges Muslims to learn foreign languages in addition to the Arabic language for various reasons including Da’wah. There is a need for Sharia graduates who have deep knowledge in religion to elevate their English proficiency to a high level. Thus, designing specific English language courses, which are related to the students’ interests, specialization, and future professions, may facilitate their learning the English Language. It could also be a source of their motivation and encouragement to improve their English proficiency. Further quantitative and qualitative researches are recommended to framework English courses for University Sharia students. This research may contribute to the development of Islamic English curriculum for Muslim students at other education levels.